Kontribusi Variabel Makroekonomi Terhadap Sukuk Perusahaan di Indonesia Periode 2011-2021 - Mulyadi, Sandi; Apriliza , Icha; Suryanto , Asep (Jurnal Ekonomika dan Bisnis Islam, 2022)
The basis of the research with the issue of research on the condition of corporate sukuk in Indonesia during the pandemic with the aim of describing the condition of macroeconomic variables on corporate sukuk in Indonesia before and during this pandemic, using macroeconomic variables proxied by Gross Domestic Product (GDP), exchange rate, Amount of Money Outstanding (JUB), Indonesian Sharia Stock Index (ISSI), interest rates, and inflation. The method used in this research is descriptive quantitative by analyzing secondary data which is processed using Eviews 10 with the VECM method and using quarterly time series data from 2011-2021. The results of data processing using VECM show several findings, namely: GDP, JUB, interest rates, and inflation variables have a negative effect, while ISSI and the exchange rate have a positive effect on corporate sukuk in the long term, while in the short term they have no significant effect on corporate sukuk in Indonesia. Meanwhile, based on testing using FEDV, the contribution to the growth of corporate sukuk is GDP (0.01%), exchange rate (2.03%), JUB (3.57%), ISSI (0.25%), interest rates (2.41%), and inflation (0.08%).